2008
DOI: 10.2967/jnumed.108.053520
|View full text |Cite
|
Sign up to set email alerts
|

MRI Reporter Genes

Abstract: Noninvasive molecular imaging of dynamic processes has benefited tremendously from the use of reporter genes. These genes encode for proteins that emit light, bind radiolabeled probes, or, as covered in this review, modulate MRI contrast. Reporter genes play a pivotal role in monitoring cell trafficking, gene replacement therapy, protein-protein interactions, neuronal plasticity, and embryonic development. Several strategies exist for generating MRI contrast: using enzyme-catalyzed chemical modification of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 27 publications
0
80
0
Order By: Relevance
“…MR imaging reporter gene methods are well suited for this purpose and are emerging alternatives to conventional cell-labeling strategies (12,13). A prominent MR imaging reporter gene method uses cellular overexpression of proteins responsible for maintaining iron homeostasis, notably ferritin, to generate R2 and/or R2* contrast on images of reporter gene-expressing cells (14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Cell Preparationmentioning
confidence: 99%
“…MR imaging reporter gene methods are well suited for this purpose and are emerging alternatives to conventional cell-labeling strategies (12,13). A prominent MR imaging reporter gene method uses cellular overexpression of proteins responsible for maintaining iron homeostasis, notably ferritin, to generate R2 and/or R2* contrast on images of reporter gene-expressing cells (14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Cell Preparationmentioning
confidence: 99%
“…87 MRI-based approaches rely on factors including: (1) enzyme-based reporter genes including β-galactosidase, which cleaves galactose form specific contrast agents; (2) expressions of surface receptors that enable binding of specific MR contrast agents; and (3) expressions of endogenous irons, such as tyrosinase, transferrin receptor, and ferritin. 88,89 Bengtsson et al 90 used lacZ as an MRI reporter gene for in vitro and in vivo MR imaging of mouse BMSCs. Chung et al 91 also reported the combination of myc and hemagglutinin A antigen-expressing reporter gene and SPIO-conjugated antibody techniques for detecting early mouse ESC-derived teratoma formation in injured mouse myocardium.…”
Section: Current Stem Cell Imaging Technologiesmentioning
confidence: 99%
“…Bulte and colleagues classiˆed 3 categories of MR imaging reporters-enzymebased, chemical exchange saturation transfer (CEST)-based, and iron-based. 35 b-Galactosidase, encoded by the bacterial gene lacZ, is suggested as an enzyme-based MR imaging reporter gene and has long been used to assess gene transfer and its expression in vivo as well as in vitro with colored substrates. 36 Taking advantage of its well established chemical reactions, gadoliniumbased MR imaging contrast agents were designed that function as substrates for b-Galactosidase.…”
Section: Mr Imaging Reporter Genesmentioning
confidence: 99%